Пятая гора: [роман] / Пауло Коэльо ; [перевод с португальского А. В. Эмин] - Коэльо Пауло (София, 2004)
Экземпляры: ф.22 (20181022) / Инвентарный номер: 58645 / Цена: / Сис.шифр: 84(7Бра)-4 / Авт.знак: К 76 / ГРНТИ: 17.82.31 / ББК: 84(7Бра)-44